Proceedings of the 2nd International Workshop & Congress on eMaintenance : Dec 12-14 Luleå, Sweden : eMaintenace: trends in technologies and methodologies, challenges, possibilities and applications - Karim, Ramin; Parida, Aditya; Kumar, Uday (Luleå tekniska universitet, Drift, underhåll och akustik, 2012)
Compilation of papers presented in the technical sessions during the eMaintenance 2012. Godkänd; 2012; 20121123 (raka)